Safety, long-term outcomes and predictors of recurrence following a single catheter ablation procedure for atrial fibrillation. Issue 4 (4th July 2019) - Efremidis, Michael; Letsas, Konstantinos P.; Georgopoulos, Stamatis; Karamichalakis, Nikolaos; Vlachos, Konstantinos; Lioni, Louiza; Bazoukis, George; Saplaouras, Athanasios; Sakellaropoulou, Antigoni; Kolokathis, Angelos Michael; Rokiza, Aikaterini; Anagnostou, Aikaterini; et al.
Abstract: Background: Data regarding long-term outcomes of atrial fibrillation (AF) catheter ablation are limited. This study evaluated the safety, long-term efficacy and predictors of recurrence after a single left atrial ablation procedure in patients with paroxysmal (PAF) and non-paroxysmal AF (NPAF). Methods: Data from 520 patients (354 males, mean age 57.08 ± 11.33 years) with PAF ( n  = 356, 68.5%) or NPAF ( n  = 164, 31.5%) who underwent a single radiofrequency ablation procedure were analysed. Across the NPAF group, there were 143 (27.5%) patients with persistent AF and 21 (4%) with long-standing persistent AF. The mean follow-up period was 39.05 ± 20.83 months (range 19–60 months). Results: Arrhythmia recurrence was observed in 102/356 (28.7%) of PAF patients and in 63/164 (38.4%) of NPAF patients. In patient with PAF, sinus rhythm maintenance was observed in 76.9%, 73% and 71.3% of patients at 1, 2 and 5 years of follow-up, respectively. In patients with NPAF, sinus rhythm was maintained in 68.7%, 63.4% and 61.6% of patients at 1, 2 and 5 years of follow-up, respectively. Independent predictors of AF recurrence were left atrial diameter (OR 1.15, 95% CI 1.10–1.21, p  < 0.01) as well as early arrhythmia recurrence during the blanking period of 3 months after the procedure (OR 8.13, 95% CI 5.10–12.82, p  < 0.01). Major complications were observed in 11 patients (2.1%). Conclusions: Long-term arrhythmia-free survival rates remain high among PAF and NPAF patients after a single catheter ablation procedure. Left atrial diameter and early arrhythmia recurrence were independent predictors of late arrhythmia recurrence in both PAF and NPAF patients.